Case Report: Hyperplastic cervical polyp with lipomatous differentiation in a dog - Song, Sunhye; Lee, Seung-Hyun; Kim, Sungsoo (Frontiers in Veterinary Science, 2025)
Uterine lesions containing adipose tissue are extremely rare in dogs, and cervical polyps are rarely reported in veterinary literature. This case report describes an 11-year-old intact female mixed-breed dog presenting with chronic vaginal discharge. Diagnostic imaging revealed a well-defined fat-attenuating mass in the cervix. The lesion appeared as a homogeneously hyperechoic intrauterine mass on ultrasonography and exhibited hypoattenuation with enhanced internal septa on computed tomography. Histopathological examination of specimens collected during ovariohysterectomy confirmed the presence of a hyperplastic polyp with prominent lipomatous differentiation arising from the cervix. The patient’s marked obesity and hypertriglyceridemia suggested a possible role of metabolic imbalance in the lesion’s development. To the best of our knowledge, this is the first veterinary report of canine lipomatous cervical polyps. This case expands the limited literature on adipose-containing uterine lesions in dogs and highlights the diagnostic value of multimodal imaging for their identification and characterization.